The P21-activated kinase PAK4 is implicated in fatty-acid potentiation of insulin secretion downstream of free fatty acid receptor 1. Issue 6 (1st November 2016) - Bergeron, Valérie; Ghislain, Julien; Poitout, Vincent
ABSTRACT: Free fatty acid receptor 1 (FFA1/GPR40) plays a key role in the potentiation of glucose-stimulated insulin secretion by fatty acids in pancreatic β cells. We previously demonstrated that GPR40 signaling leads to cortical actin remodeling and potentiates the second phase of insulin secretion. In this study, we examined the role of p21 activated kinase 4 (PAK4), a known regulator of cytoskeletal dynamics, in GPR40-dependent potentiation of insulin secretion. The fatty acid oleate induced PAK4 phosphorylation in human islets, in isolated mouse islets and in the insulin secreting cell line INS832/13. However, oleate-induced PAK4 phosphorylation was not observed in GPR40-null mouse islets. siRNA-mediated knockdown of PAK4 in INS832/13 cells abrogated the potentiation of insulin secretion by oleate, whereas PAK7 knockdown had no effect. Our results indicate that PAK4 plays an important role in the potentiation of insulin secretion by fatty acids downstream of GPR40.